The Holy Spirit, Eco‐Justice, and an African Lutheran Response to Ecological Peril. Issue 3 (September 2016) - Lugazia, Faith K.
Abstract: In response to the environmental degradation that is taking place right now in much of Africa—and in light of a traditional African emphasis on interdependence—this article seeks to provide an African Lutheran "eco‐pneumatological" contribution to the ongoing conversation about eco‐justice. To do so, it draws on classic Lutheran understandings of creation and grace, even as it calls for a more expanded—and more deeply biblical—understanding of the Holy Spirit's presence and activity throughout all of creation.